THE EFFECTS OF PHYSIOLOGICAL CHANGES ON EMOTIONS DURING POSTPARTUM PERIOD - Abdullah, Maisarrah; Sailin, Siti Nurul Safiah Mohd; Elham, Fahirah Nurdini Mohd Yazil; Affendy, Amni Adlina; Radhyani, Fathya; Che Mohd Nassir, Che Mohd Nasril; Ahmed, Mohamed Ayaaz; Md Tajudin, Huriyyah Hamiemah; Jaffer, Usman (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
In this writing, we aspire to look into the effects of physiological changes during postpartum on emotions. It is found that postpartum depression has affected about 27% of Malaysian women. Therefore, in this review, we have looked into three different aspects which are: 1) hormonal changes 2) neurotransmitters, and 3) biological changes. These topics are studied to see how they affect the emotions among women during the postpartum period. It has been found that they may fall into an emotional state, depressive state or even become anxious when physiological changes happen. This writing also provided the treatments for certain issues while looking into the Islamic perspective and Islamic treatment that can help reduce the symptoms. It also emphasizes the need for more research on the topic to provide more explanations and interventions to help those suffering from baby blues syndrome.